Identification Of sRNA Mediated Responses To Nutrient Depletion In Burkholderia Pseudomallei - Hirzahida Mohd-Padil; Nadzirah Damiri; Suhaila Sulaiman; Shiao-Fei Chai; Sheila Nathan; Mohd Firdaus-Raih (Nature Research, 2024)
Indexed by SCOPUS